GNPF MUI: STRATEGI PEMBINGKAIAN DAN KEBERHASILAN GERAKAN POPULIS ISLAM DI INDONESIA - Fathy, Rusydan (ASKETIK: Jurnal Agama dan Perubahan Sosial, 2019)
Armed with a social movement approach, this paper discusses the framing strategy in the success of the Islamic populist movement in Indonesia. Islamic populism coloring political life and democracy in Indonesia in recent years. As with other forms of populist movements, Islamic populism in Indonesia manifests itself in mass movements or actions that show protest or resistance to certain regimes and government systems. The emergence of the Gerakan Nasional Pengawal Fatwa Majelis Ulama Indonesia (GNPF-MUI/Guard National Movement for Indonesian Religious Leader) includes the 411, 212 movement, and the grand reunion of 212 alumni is a manifestation of the rise of Islamic populism in Indonesia.